Polyphenyl ether composition as well as preparation method and application thereof
By adjusting the zero-shear viscosity and glass fiber retention length of the polyphenylene ether composition, combined with a specific phosphorus-containing flame retardant, the problem of insufficient melt strength of the polyphenylene ether-nylon plastic alloy in high temperature ablation is solved, and polypolytic is achieved The excellent ablation resistance of the phenyl ether composition is suitable for high-demand occasions such as the power battery cover of new energy vehicles.
Patent Information
- Application Number
- CN202411531597.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing polyphenylene ether-nylon plastic alloy has low melt strength during high-temperature ablation, which cannot meet the long-term high-temperature ablation requirements, especially in the cover materials of power batteries of new energy vehicles. .
By adjusting the zero-shear viscosity of the polyphenylene ether composition and the average retention length of glass fibers and using a specific combination of phosphorus-containing flame retardant, a stable carbon layer is formed to enhance melt strength and flame retardant properties, ensuring that the material is at high temperatures No perforation and collapse occur, while improving the retention length and dispersion effect of glass fibers.
The polyphenylene ether composition has excellent ablation resistance at high temperatures, avoids perforation and collapse, and meets the flame retardant and ablation resistance requirements in high demand occasions such as power battery covers.
Smart Images

Figure BDA0005110598010000071 
Figure BDA0005110598010000072 
Figure BDA0005110598010000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering plastics, and more specifically, relates to a polyphenylene ether composition and a preparation method and application thereof. Background Art
[0002] Polyphenylene ether (PPE) is an engineering plastic with excellent comprehensive performance, with the characteristics of high strength, high rigidity, high heat resistance and low smoke density. At the same time, PPE also has some disadvantages, such as poor processability and solvent resistance, which limit its application in high-demand occasions. However, PPE can be blended with polyamide (PA) to prepare alloys, which can well achieve the complementary performance of the two materials and is widely used in electronic appliances, automobiles and other fields.
[0003] According to GB / T 38031-2020 "Safety Requirements for Power Batteries for Electric Vehicles", new energy vehicle power battery covers have high requirements for the flame retardancy and ablation resistance of materials. In order to meet the demand for plastics to replace steel in battery cover materials, ablation-resistant PPE-PA compositions have good application prospects.
[0004] Patent CN116253982A discloses a flame retardant, weather resistant and heat resistant polyphenylene ether-nylon plastic alloy, comprising the following components: polyphenylene ether, nylon, flame retardant, compatibilizer, antioxidant, and light stabilizer. The antioxidant comprises two or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, bis(2,4-dicumylphenyl) pentaerythritol diphosphite and pentaerythritol dodecylthiopropyl ester. Although the above polyphenylene ether-nylon plastic alloy achieves V-0 level flame retardancy, the melt strength is low and it is completely unable to meet the requirements of long-term high temperature ablation. Therefore, how to provide a polyphenylene ether composition with excellent burning resistance becomes a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above existing technical problems, the primary purpose of the present invention is to provide a polyphenylene ether composition, which has good ablation resistance.
[0006] The second object of the present invention is to provide a method for preparing the polyphenylene ether composition.
[0007] The third object of the present invention is to provide an application of the polyphenylene ether composition in the field of electronic appliances or automobiles.
[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0009] A polyphenylene ether composition comprises the following components by weight: 9-26 parts of PPE resin, 19-41 parts of PA resin, 5-10 parts of phosphorus-containing flame retardant A, 2-6 parts of phosphorus-containing flame retardant B, 5-15 parts of compatibilizer, and 10-40 parts of glass fiber; the zero shear viscosity of the polyphenylene ether composition is 10000-100000 Pa·s; the average retention length of the glass fiber is 0.2-0.35 mm; the phosphorus-containing flame retardant A is selected from one or more of hypophosphite flame retardants, red phosphorus, and polyphosphate flame retardants; and the phosphorus-containing flame retardant B is selected from one or more of phosphate flame retardants and phosphazene flame retardants.
[0010] During the high-temperature ablation process of the polyphenylene ether composition, the surface of the material is burned into carbon while the matrix is heated, melted and deformed. When the carbon layer is not sufficient to support the flow of the melt under gravity, the material will be perforated, resulting in ablation resistance failure.
[0011] The inventors have found through research that the zero shear viscosity of the composition and the average retention length of the glass fibers jointly affect the melt strength.
[0012] When the zero shear viscosity of the prepared polyphenylene ether composition is within the above range, the polyphenylene ether composition can maintain a certain melt strength, which is conducive to ensuring that the melt forms a stable carbon layer during the high-temperature burning process, avoiding collapse and perforation; at the same time, the above zero shear viscosity range can meet the requirements of the polyphenylene ether composition for fluidity during the molding process, ensuring that the flame retardant is evenly dispersed in the resin matrix, and can also reduce the shear effect of the resin on the glass fiber during the co-extrusion process, and increase the average retention length of the glass fiber. The specific average retention length of the glass fiber can form a continuous and stable three-dimensional network of glass fibers in the polyphenylene ether-polyamide system, thereby improving the melt strength of the system. If the average retention length of the glass fiber is too long, it means that the shear force is too small, and the material is not completely plasticized, resulting in a decrease in ablation resistance; if the average retention length of the glass fiber is too short, it cannot play an effective reinforcing role in the melt, which will cause the flame retardant ability to fail during the ablation process.
[0013] Furthermore, the inventors found through research that the average retention length of glass fibers and a specific combination of phosphorus-containing flame retardants jointly affect the thickness of the carbon layer.
[0014] Glass fibers with a specific average retention length can improve the melt strength of the polyphenylene ether-polyamide system while also effectively dispersing and conducting heat, which can reduce the thermal degradation of the system and ensure the formation of a stable carbon layer, thereby improving the material's ablation resistance. Specific phosphorus-containing flame retardants A and phosphorus-containing flame retardants B are used in combination. Phosphorus-containing flame retardant A decomposes at high temperatures to produce free radicals, which can capture the free radicals produced during the combustion process, thereby interrupting the chain reaction of combustion and promoting the rapid carbonization of the polymer to form a carbon layer. The synergistic effect of phosphorus-containing flame retardant B can further improve the flame retardant efficiency, and the decomposed substances will form a non-volatile protective film on the basis of the original carbon layer, thereby enhancing the strength of the carbon layer, improving the oxygen and heat insulation effects, and achieving excellent ablation resistance of the material.
[0015] The present invention provides a polyphenylene ether composition. By controlling the zero shear viscosity of the polyphenylene ether composition, the average retention length of glass fibers, and specific phosphorus-containing flame retardants A and B, and matching a compatibilizer in the system, the prepared polyphenylene ether composition has good ablation resistance.
[0016] Specifically, the mass percentage of the PPE resin in the polyphenylene ether composition is not less than 7.4%. More preferably, the mass percentage of the PPE resin in the polyphenylene ether composition is not less than 11.6%.
[0017] Specifically, the mass percentage of the PA resin in the polyphenylene ether composition is not less than 16.3%. More preferably, the mass percentage of the PA resin in the polyphenylene ether composition is not less than 19.6%.
[0018] Specifically, the PPE resin can be 12 parts, 15 parts, 18 parts, 21 parts, 23 parts, 25 parts, etc., or an interval range formed by any of the above values; the PA resin can be 21 parts, 23 parts, 25 parts, 27 parts, 29 parts, 31 parts, 33 parts, 35 parts, 37 parts, 40 parts, etc., or an interval range formed by any of the above values; the glass fiber can be 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, etc., or an interval range formed by any of the above values.
[0019] Specifically, the zero shear viscosity of the polyphenylene ether composition is 12000-81000 Pa·s; and the average retention length of the glass fiber is 0.230-0.312 mm.
[0020] Specifically, the zero shear viscosity of the polyphenylene ether composition can be 20000Pa·s, 30000Pa·s, 40000Pa·s, 50000Pa·s, 60000Pa·s, 70000Pa·s, 80000Pa·s, 90000Pa·s, etc., or an interval range formed by any of the above values, such as 45000-71000Pa·s, 40000-80000Pa·s, etc., and the present invention is not limited thereto. The test method for the zero shear viscosity of the polyphenylene ether composition is: testing using a rotational rheometer, and specific reference can be made to JY / T0590-2020 "General Rules for Rotational Rheometer Measurement Methods".
[0021] Specifically, the average retention length of the glass fiber in the present invention can be 0.22mm, 0.24mm, 0.26mm, 0.28mm, 0.30mm, 0.32mm, 0.34mm, etc., or an interval range formed by any of the above values, such as 0.24-0.28mm, 0.26-0.32mm, etc., and the present invention is not limited thereto. The test method for the average retention length of the glass fiber is: optical microscope-image analyzer method. More specifically, the test method can be tested with reference to the method disclosed in patent CN 109164106 A. Those skilled in the art can adjust the average retention length of the glass fiber by conventional technical means in the art; for example, resins of different viscosities can be used, and resins of different viscosities will affect the shear strength during processing, thereby affecting the average retention length of the glass fiber; for example, it can be added from different feeding ports of the screw extruder to adjust the average retention length of the glass fiber.
[0022] Specifically, the intrinsic viscosity of the PA resin is 1.5-3.0 dL / g. The intrinsic viscosity of the PA resin is tested by an Ubbelohde viscometer, with sulfuric acid as the solvent.
[0023] Specifically, the intrinsic viscosity of the PPE resin is 0.4-0.45 dL / g. The intrinsic viscosity of the PPE resin is tested by an Ubbelohde viscometer, with chloroform as the solvent.
[0024] Preferably, the phosphorus-containing flame retardant A is selected from one or more of diethyl aluminum hypophosphite, diethyl zinc hypophosphite, phenyl aluminum hypophosphite, red phosphorus, and ammonium polyphosphate.
[0025] Preferably, the phosphate flame retardant is selected from one or more of triphenyl phosphate, tricresyl phosphate, tributyl phosphate, trioctyl phosphate, tolyl diphenyl phosphate, and isopropylated triphenyl phosphate; and / or
[0026] The phosphazene flame retardant is selected from one or more of hexaphenoxy cyclotriphosphazene, hexachlorocyclotriphosphazene and their derivatives.
[0027] Preferably, the compatibilizer is one or more of PPE grafts, SEBS grafts, and POE grafts; the grafted portion of the PPE grafts, SEBS grafts, and POE grafts is selected from one or more of maleic anhydride, fumaric anhydride, citric acid, and unsaturated dicarboxylic acids.
[0028] Preferably, the grafting rate of the PPE graft, SEBS graft, and POE graft is 0.6 to 3.5%. Further preferably, the grafting rate is 0.6 to 1.5%. Under this preference, the polyphenylene ether composition has better melt strength and mechanical properties. More specifically, the grafting rate in the present invention can be 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, etc., or an interval range formed by any of the above values, such as 0.6 to 1.3%, 0.9 to 1.7%, etc., and the present invention is not limited thereto. More specifically, the test method for the grafting rate is: infrared spectroscopy.
[0029] Preferably, the PA resin is selected from one or more of PA6 resin, PA46 resin, PA66 resin, PA610 resin, PA612 resin, PA66 / 6T resin, and PA6I / 6T resin. Further preferably, the PA resin is PA66 resin and / or PA66 / 6T resin.
[0030] Preferably, the glass fiber has a diameter ranging from 8 to 15 μm and a length ranging from 2 to 5 mm.
[0031] Preferably, the polyphenylene ether composition further comprises one or more of lubricants, mineral powders, and colorants. Among them, lubricants include but are not limited to polyethylene wax, zinc stearate, lithium stearate, etc. Mineral powders include but are not limited to talc, calcium carbonate, kaolin, mica powder, barium sulfate, etc. Colorants include but are not limited to carbon black, titanium dioxide, zinc sulfide, titanium yellow, iron red, etc.
[0032] Furthermore, the present invention claims protection for a method for preparing a polyphenylene ether composition, wherein PPE resin, PA resin, compatibilizer, phosphorus-containing flame retardant A, and phosphorus-containing flame retardant B are mixed and extruded, and glass fiber is added from a side feed port and extruded to obtain the polyphenylene ether composition.
[0033] Preferably, a twin-screw extruder is used for extrusion, and the aspect ratio of the twin-screw extruder is 40 to 56:1.
[0034] Preferably, the screw speed of the twin-screw extruder is 300-1000 rpm.
[0035] Preferably, the extrusion temperature is 250-280°C.
[0036] Furthermore, the present invention claims a polyphenylene ether composition for use in the field of electronic appliances or automobiles. Specifically, the polyphenylene ether composition is suitable for power battery brackets, cover plates and boxes, IGBT modules, high-voltage connectors, etc., especially for applications with high requirements for burn resistance.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The present invention provides a polyphenylene ether composition. By controlling the zero shear viscosity of the polyphenylene ether composition, the average retention length of glass fibers, and specific phosphorus-containing flame retardants A and B, and matching a compatibilizer in the system, the prepared polyphenylene ether composition has good ablation resistance. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the specification and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0040] The raw materials of the embodiments and comparative examples are as follows:
[0041] PPE resin 1, intrinsic viscosity 0.4 dL / g, PPE LXN040, Nantong Xingchen Synthetic Materials Co., Ltd.
[0042] PPE resin 2, intrinsic viscosity 0.43 dL / g, XYRON S201A, Asahi Chemical, Japan.
[0043] PPE resin 3, intrinsic viscosity 0.45 dL / g, PPE ZM045, Dalian Zhongmu Chemical Co., Ltd.
[0044] PPE resin 4, intrinsic viscosity 0.35 dL / g, PPE LXN035, Nantong Xingchen Synthetic Materials Co., Ltd.
[0045] PPE resin 5, intrinsic viscosity 0.5 dL / g, PPE LXN050, Nantong Xingchen Synthetic Materials Co., Ltd.
[0046] PA resin 1, PA6, intrinsic viscosity 2.4 dL / g, HY-2500A, Jiangsu Haiyang Chemical Fiber Co., Ltd.
[0047] PA resin 2, PA66, intrinsic viscosity 2.4 dL / g, PA66 U3600 NC01 SS, INVISTA Nylon Chemical (China) Co., Ltd.
[0048] Phosphorus-containing flame retardant A, diethyl aluminum hypophosphite, EXOLIT OP 1230, Clariant Chemicals Co., Ltd.
[0049] Phosphorus-containing flame retardant B1, hexaphenoxy cyclotriphosphazene, HPCTP, Hongda Dante Chemical Co., Ltd.
[0050] Phosphorus-containing flame retardant B2, triphenyl phosphate, WSFR-TPP, manufacturer Zhejiang Wansheng Technology Co., Ltd.
[0051] Flame retardant 1, magnesium hydroxide, Aitemag 12FD, Jiangsu Aitek Flame Retardant Material Co., Ltd.
[0052] Flame retardant 2, brominated polystyrene, BPS HM-20, Weifang Shuangfeng Chemical Co., Ltd.
[0053] Glass fiber, ECS10-03-568H, China Jushi Co., Ltd.
[0054] Compatibilizer 1, PPE grafted with maleic anhydride, the grafting rate of maleic anhydride is 1.5%. The preparation of compatibilizer 1 is as follows: 3% by mass of maleic anhydride is blended and extruded with PPE resin 1; the aspect ratio of the twin-screw extruder is 56:1; the screw speed of the twin-screw extruder is 600 rpm; and the extrusion temperature is 280°C.
[0055] Compatibilizer 2, PPE grafted with maleic anhydride, the grafting rate of maleic anhydride is 0.6%. Preparation method of compatibilizer 2: Referring to the preparation method of compatibilizer 1, maleic anhydride with a mass fraction of 1.5% is blended and extruded with PPE resin 1 to obtain the compatibilizer.
[0056] Compatibilizer 3, PPE grafted with maleic anhydride, the grafting rate of maleic anhydride is 2.0%. Preparation method of compatibilizer 3: Referring to the preparation method of compatibilizer 1, 5% by mass of maleic anhydride and PPE resin 1 are blended and extruded to obtain the compatibilizer.
[0057] Compatibilizer 4, POE grafted product, POE-g-MAH, grafting rate 3.5%, FB521A, Jiayirong Polymer (Shanghai) Co., Ltd.
[0058] Unless otherwise specified, the components used in the parallel embodiments and comparative examples are all the same commercially available products.
[0059] Example 1
[0060] The weight parts of the raw materials used in Example 1 are shown in Table 1.
[0061] A method for preparing a polyphenylene ether composition, the specific steps comprising:
[0062] PPE resin, PA resin, compatibilizer, phosphorus-containing flame retardant A, and phosphorus-containing flame retardant B are added to a high-speed mixer and mixed evenly to obtain a uniformly mixed material. The uniformly mixed material is added to a twin-screw extruder (with a length-to-diameter ratio of 56:1 and a rotation speed of 600 rpm) through a main feeding port, and glass fiber is added to the extruder from a side feeding port and extruded (280° C.) and granulated to obtain a polyphenylene ether composition.
[0063] Example 2 to Example 11
[0064] The weight parts of the raw materials used in the following examples are shown in Table 1.
[0065] The specific preparation steps of the following examples are the same as those of Example 1.
[0066] Comparative Example 1 to Comparative Example 8
[0067] The weight parts of the raw materials used in the following comparative examples are shown in Table 2.
[0068] Adding glass fiber from the main feed port will cause the glass fiber to be more broken. Therefore, in order to obtain a shorter average retention length of the glass fiber, the difference between Comparative Example 6 and Example 1 is that the glass fiber is added to the extruder from the main feed port and then extruded.
[0069] The specific preparation steps of other comparative examples are the same as those of Example 1.
[0070] Table 1
[0071]
[0072] Table 2 shows the formula components of each comparative example:
[0073] Table 2
[0074]
[0075]
[0076] The polyphenylene ether compositions prepared in the above examples and comparative examples were tested using the following test methods.
[0077] Zero shear viscosity: The zero shear viscosity of the polyphenylene ether composition obtained by extrusion was tested using a rotational rheometer at 300° C. and a shear rate of 0.1 rad / s.
[0078] Notched impact strength: Injection molded specimens of polyphenylene ether composition, tested in accordance with ISO 180:2019.
[0079] High temperature flexural modulus: Polyphenylene ether composition injection molded specimens, tested in accordance with ISO 178::2019, the test temperature is 105℃.
[0080] Average retention length of glass fibers: The average retention length of glass fibers in the extruded polyphenylene ether composition was tested according to the method disclosed in patent CN 109164106A.
[0081] Ablation resistance: The polyphenylene ether composition is injection molded into a 2*150*150mm square plate, placed horizontally and flame-ablated at 1000℃ for 10 minutes to observe whether there is dent or burn-through. Among them, qualified means: no dent or burn-through occurs; unqualified means: dent and / or burn-through occurs.
[0082] Melt Strength: The melt strength of the polyphenylene ether composition obtained by extrusion was tested online using a Haake torque rheometer.
[0083] Table 3 and Table 4 are the performance test results of each embodiment and comparative example respectively.
[0084] Table 3
[0085]
[0086] Table 4
[0087]
[0088] It can be seen from the data of the examples that the present invention provides a polyphenylene ether composition, when the average retention length of the glass fiber is 0.2 to 0.35 mm and the zero shear viscosity of the polyphenylene ether composition is 10,000 to 100,000 Pa·s, the polyphenylene ether composition has excellent melt strength and ablation resistance. When the polyphenylene ether composition is flame-ablated at 1000°C for 10 minutes in a horizontal position, no dent or burn-through occurs; and the melt strength is ≥32 cN. More preferably, the melt strength is ≥49 cN.
[0089] It can be seen from Example 1, Example 5 and Example 6 that when the grafting rate of the grafted species in the compatibilizer is within a preferred range, the polyphenylene ether composition has better melt strength and mechanical properties.
[0090] It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that when the zero shear viscosity of the polyphenylene ether composition is within the range of 10000 to 100000 Pa·s, no sinking and burning-through phenomena will occur in the burning resistance test.
[0091] It can be seen from Example 1, Comparative Example 3, Comparative Example 4, Comparative Example 7 and Comparative Example 8 that when no specific flame retardant is used in the polyphenylene ether composition system, even if it has acceptable melt strength, its char layer strength is still insufficient, the polyphenylene ether composition will experience depression and burn-through, and the ablation resistance effect is unsatisfactory.
[0092] It can be seen from Example 1 and Comparative Example 6 that in the polyphenylene ether composition, when the average retention length of the glass fiber is in the range of 0.2 to 0.35 mm, the polyphenylene ether composition has excellent burn resistance. When the average retention length of the glass fiber is lower than the above range, the polyphenylene ether composition will have dents and burn-through phenomena.
[0093] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. A polyphenylene ether composition, characterized in that By weight, it includes the following components: PPE resin 9-26 parts, PA resin 19-41 parts, phosphorus-containing flame retardant A 5-10 parts, phosphorus-containing flame retardant B 2-6 parts, compatibilizer 5-15 parts, glass fiber 10-40 parts; The zero shear viscosity of the polyphenylene ether composition is 10000 to 100000 Pa·s; The average retention length of the glass fiber is 0.2 to 0.35 mm; The phosphorus-containing flame retardant A is selected from one or more of hypophosphite flame retardants, red phosphorus, and polyphosphate flame retardants; the phosphorus-containing flame retardant B is selected from one or more of phosphate flame retardants and phosphazene flame retardants.
2. The polyphenylene ether composition according to claim 1, characterized in that: The zero shear viscosity of the polyphenylene ether composition is 12000-81000 Pa·s; and the average retention length of the glass fiber is 0.230-0.312 mm.
3. The polyphenylene ether composition according to claim 1, characterized in that: The phosphorus-containing flame retardant A is selected from one or more of diethyl aluminum hypophosphite, diethyl zinc hypophosphite, phenyl aluminum hypophosphite, red phosphorus, and ammonium polyphosphate.
4. The polyphenylene ether composition according to claim 1 or 3, characterized in that: The phosphate flame retardant is selected from one or more of triphenyl phosphate, tricresyl phosphate, tributyl phosphate, trioctyl phosphate, tolyl diphenyl phosphate, and isopropylated triphenyl phosphate; and / or The phosphazene flame retardant is selected from one or more of hexaphenoxy cyclotriphosphazene, hexachlorocyclotriphosphazene and their derivatives.
5. The polyphenylene ether composition according to claim 1, characterized in that: The compatibilizer is one or more of PPE grafts, SEBS grafts, and POE grafts; the grafted parts of the PPE grafts, SEBS grafts, and POE grafts are selected from one or more of maleic anhydride, fumaric anhydride, citric acid, and unsaturated dicarboxylic acids.
6. The polyphenylene ether composition according to claim 5, characterized in that: The grafting rates of the PPE grafts, SEBS grafts and POE grafts are 0.6-3.5%.
7. The polyphenylene ether composition according to claim 1, characterized in that: The PA resin is selected from one or more of PA6 resin, PA46 resin, PA66 resin, PA610 resin, PA612 resin, PA66 / 6T resin, and PA6I / 6T resin.
8. The polyphenylene ether composition according to claim 1, characterized in that: The polyphenylene ether composition comprises one or more of a lubricant, a mineral powder and a colorant.
9. The method for preparing the polyphenylene ether composition according to any one of claims 1 to 8, characterized in that: The PPE resin, PA resin, compatibilizer, phosphorus-containing flame retardant A and phosphorus-containing flame retardant B are mixed and extruded, and glass fiber is added and extruded from a side feeding port to obtain the polyphenylene ether composition.
10. Use of the polyphenylene ether composition according to any one of claims 1 to 8 in the field of electronic appliances or automobiles.
Citation Information
Patent Citations
Test method of glass fiber reservation length of glass fiber reinforced hot-moulding composite
CN109164106A
Thin-wall flame-retardant PA-PPE composition as well as preparation method and application thereof
CN116102876A
Red phosphorus flame-retardant non-reinforced nylon / polyphenyl ether alloy material and preparation method thereof
CN116875046A
Compatibilized polyphenylene ehter resin / nylon resin blends containing aromatic phosphorous-containing compounds
EP0436136A1
Reinforced resin composition having surface
JP1994220318A
Cited By
Polyamide composite material, preparation method thereof and connector
CN121628364A